Inflation, unemployment and the position of the central bank: the opinion of the public - PRAST, H.M. (PSL Quarterly Review, 2013)
Recent theoretical developments in monetary policy are based on the view that the effectiveness of monetary policy is strongly influenced by the interaction between the behaviour of the monetary policy-makers and the private sector. Optimal monetary policy and the possible desirability of central bank independence are directly related to respective assumptions about the information and opinion of the private sector. These assumptions are tested in Italy and the Netherlands. Surveys conducted through telephone and face-to-face interviews show central bank independence and future inflation estimates that are higher among people with higher education and lower for those with lower education. Also revealed is a central bank that is more concerned with unemployment and a government that is concerned with inflation. The glaring result, however, is the public's lack of awareness about a trade-off between inflation and unemployment. JEL Codes: E52, E58